Physicochemical and Pharmacological Investigation of Water/Oil Microemulsion of Non-Selective Beta Blocker for Treatment of Glaucoma. (February 2014) - Hegde, Rahul Rama; Bhattacharya, Shiv Sankar; Verma, Anurag; Ghosh, Amitava
Abstract Purpose: Ocular drug delivery system always remained associated with lots of difficulties and faced issues of poor drug absorption and poor bioavailability. Timolol maleate is a nonspecific beta blocker used for reduction of elevated intraocular pressure in glaucoma. Timolol maleate is absorbed systemically and is contraindicated in asthmatic patients. This study is focused to deliver Timolol maleate by a water/oil microemulsion to extend the time of reduced intraocular pressure of glaucomatous rabbit's eye measured by using a schoetz tonometer. Methods: The microemulsion is prepared by mixing the oily components with two nonionic surfactants, drug and water, and evaluated for the physicochemical, in vitro and in vivo parameters. Results: The colloidal system demonstrates monodisperse distribution behavior and exhibits a uniform size distribution of finite width. In vitro drug release from microemulsion was found to follow Higuchi's pattern followed by a zero-order drug release by the emulsion. Ex vivo permeation through goat cornea revealed delayed release of Timolol maleate from microemulsion as compared with its aqueous solution. A reduction in intraocular pressure is seen lasting for 12 h compared to aqueous eye drop that lasted for only 5 h. Conclusion. In vivo reduction of intraocular pressure revealed a similar efficacy for once daily dosed 0.3% Timolol maleate in microemulsion formulation compared to 0.5% concentration in both microemulsion as well as aqueous formulation. The possible outcome of dose reduction will reduce the cardiovascular side effects generally reported with Timolol maleate eye drops.